PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION TERHADAP HASIL BELAJAR PADA MATA PELAJARAN DASAR LISTRIK DAN ELEKTRONIKA KELAS X JURUSAN TEKNIK AUDIO VIDEO DI SMK NEGERI 1 KINALI - P. Sultan Mustika; Hanesman Hanesman; Sukaya Sukaya (Universitas Negeri Padang, 2017)
The problem in this study is the low average student learning outcomes in the Elementary Electrical and Electronics subjects is under the completeness of Learning (KB) which has been established SMK Negeri 1 Kinali is 75. This study aims to determine the influence of cooperative learning model type Assisted Team Individualization with Problem Based Learning learning model on learning outcomes in Electrical and Electronics Elementary subjects of X class students majoring in audio video engineering at SMK Negeri 1 Kinali. This type of research is an experimental research with Post-Test Design Only Group Design. The research sample is class X TAV.1 as experiment class using Team Assisted Individualization and class X TAV.2 model as control class using Problem Based Learning model. Technique of collecting data from post-test every meeting in experiment class and control class, then analyzed for homogeneity test, normality test and hypothesis test. From the experimental class research results obtained an average value of 83.57, while the control class get an average value of 76.67. The result of hypothesis calculation at significant level α = 0,05 got tcount> ttable that is 6,24> 1,674, because big tcount of ttable, null hypothesis (H0) rejected and alternative hypothesis (Ha) accepted. Can be concluded means at the real level, this study shows that, there is influence of positive learning outcomes between the use of cooperative learning model type Assisted Individualization Team with the model of Problem Based Learning in Electrical and Electronics Elementary students X class students majoring in audio video engineering at SMK Country 1 Kinali. So the results of student learning Team Assisted Individualization better in comparison with the results of student learning Problem Based Learning.. Keywords: Team Assisted Individualization, Problem Based Learning, Post-Test Only Group Design, Learning Outcomes, Experiments, Controls.